Accurate Elemental Analysis of Metal-Containing Polymer Latexes Using ICP-Optical Emission Spectrometry - Vogel, Nicolas; et al. (Macromolecular Chemistry and Physics, 2010)
The use of ICP-OES to determine the metal content of metal-complex-containing colloidal dispersions is explored. Colloidal dispersions containing a defined amount of metal complex were produced by miniemulsion polymerization. It was found that simple ICP-OES measurements yielded apparent metal concentrations significantly below the expected value. To examine the behavior of the colloidal dispersions in the ICP spectrometer, a systematic study on measurement conditions was performed. It was found that the addition of a surfactant to both colloidal dispersions and standards led to measured metal contents close to the theoretical value. Most reliable results were obtained using SDS in concentrations above the cmc.
Keywords: colloids; hybrid nanoparticles; ICP-OES; miniemulsions; surfactants